Filipino heritage the making of a nation (Manila Felta Multimedia Center, 2004)
A ten-volume study on Philippine culture and history.
CDROM
Originally published in print in 1977 by Lahing Pilipino Publishing whom Alfredo R. Roces was the editor in chief.
V.1. The stone age in the Philippines--v.2. The metal age in the Philippines--v.3. The age of trade and contacts--v.4. The Spanish colonial period : the day of the conquistador--v.5. The Spanish colonial period : under the Church bells--v.6. The Spanish colonial period : roots of national identity--v.7. The Spanish colonial period : the awakening--v.8. The period of armed stuggle--v.9. The American colonial period--v.10. Birth of a nation.
Keywords: Philippines -- History; Philippines -- Social life and customs